Semi‐conductive, Switchable Dielectric and Photoluminescent Properties of Two High‐Temperature Phase Transition Hybrids. Issue 22 (27th September 2021) - Ying, Tingting; Li, Yukong; Song, Ning; Tan, Yuhui; Tang, Yunzhi; Zhuang, Jiachang; Zhang, Hao; Wang, Lijuan
Abstract: Bistable switches (electrical switching between "ON" and "OFF" bistable states) have gradually developed into an ideal category of highly intelligent materials, due to their significant applications in optical technology, signal processors, data storage and other switchable media applications in the field of electrical devices. Here, we successfully designed and synthesized [(FC6 H4 C2 H4 NH3 )2 MCl4 ]n (FC6 H4 C2 H4 NH3 + )=deprotonated 4‐fluoro‐ phenethylamine; M=Cd (1 ), Mn (2 )), which realized the coupling of thermo‐dielectric switching characteristics, semi‐conductor characteristics and photo‐luminescent properties. DSC (differential scanning calorimetry) and dielectric measurements show that 1 is a sensitive dielectric bistable switch between the high dielectric (ON) and low dielectric (OFF) states. The temperature‐variable single crystal structure shows that the both 1 and 2 undergo a high‐temperature reversible phase transition around 383 K/380 K, which is caused by the order‐disordered transformation of organic cations and the slight distortion of the inorganic framework. In particular, 1 shows outstanding switchable dielectric behavior and semiconducting properties. Further, 1 and 2 emit strong green and yellow luminescence at 527 and 595 nm, respectively. Abstract : We successfully designed and synthesized two organic‐inorganic hybrids [(FC6 H4 C2 H4 NH3 )2 CdCl4 ]n (FC6 H4 C2 H4 NH3 = deprotonated 4‐fluorophenethylamine; M=Cd (1 ), Mn (2 )), which realized the coupling of thermo‐dielectric switching characteristics, semiconductor characteristics and photoluminescent properties.